Real time implementation of fuzzy gain-scheduled PID controller for twin rotor MIMO system (TRMS) - Mohammed Zinelaabidine, Ghellab (Université de M'sila, 2018)
The work has done in this paper concern a strategy of control based on gain adaptive proportional integral derivative (PID) using the fuzzy inference system and their application to the Twin Rotor MIMO System (TRMS), the PID controller with fixed parameters may fail to provide acceptable control performance. To improve the PID control effect, new designs of the fuzzy gain Scheduled PID controller (FGSPID) were presented in this paper. The proposed techniques were applied to the TRMS, where adaptive PID controllers were proposed for control system in the presence of external disturbances. The parameters of PID controller were adjusted by a fuzzy system, used to tune in real-time the controller gain. The obtained simulation and experiment results show that the robustness of TRMS angles (pitch and yaw) driven by proposed controller are guaranteed.
Keywords: gain-adaptive PID, FGSPID, TRMS model, fuzzy system, PID control